Phytotoxic neo-clerodane diterpenoids from the aerial parts of Scutellaria barbata. (March 2020) - Li, Hang-Ying; Wei, Wen-Jun; Ma, Kai-Liang; Zhang, Jie-Yao; Li, Ya; Gao, Kun
Abstract: Bioactivity guided the isolation of extracts from the aerial parts Scutellaria barbata D. Don to discover neo -clerodane diterpenoids with potent phytotoxic activity. Of the 34 isolates, 13 neo -clerodane diterpenoids were described for the first time. The structures of these undescribed compounds were elucidated by extensive analysis of NMR spectroscopic data, and the absolute configurations of scutebarbolides A and L and scutebata W were determined by X-ray diffraction. The phytotoxic activity of all compounds against the growth of the roots and shoots of L. perenne and L. sativa seedlings were first reported, and some compounds showed considerable inhibitory effects, especially scutebarbolide K, whose inhibition rates were higher than those of the positive control at concentrations ranging from 25 to 200 μ g/mL. When L. perenne and L. sativa seedlings were treated at a concentration of 200 μ g/mL, scutebarbolide K caused wilting symptoms on and finally death of these two tested plant seedlings. In addition, the structure-activity relationships of these neo -clerodane diterpenoids were also discussed. Graphical abstract: neo-clerodane diterpenoids from the aerial parts of S. barbata, collected in Henan Province, China. Image 1 Highlights: The aerial parts of Scutellaria barbata afforded 13 undescribed neo-clerodane diterpenoids. The absolute configurations of scutebarbolides A and L and scutebata W were determined by X-ray diffraction. Phytotoxic activity of undescribed scutebarbolide K was stronger than that of the positive control. The structure-activity relationships of these neo-clerodane diterpenoids were discussed.